Pengembangan Ekonomi Masyarakat Melalui Pembuatan WA Group Bisnis dalam Meningkatkan Pemasaran Ibu-Ibu di Perumahan Puri Depok Mas, Depok - Cempaka, Laras (LPkM Universitas Bakrie, 2021)
Economic activities in society during this pandemic need to be increased. Among them is by moving the economy from small community groups in residential areas. There is a huge opportunity for economic activity in today's residential areas, especially after the government adopted the PSBB (Large-Scale Social Restriction) policy, which in the end, many community activities were transferred to their respective areas of residence. This is an opportunity for the surrounding community to build their economic passion. One of the strategies is to create a forum in order to improve marketing, increase capabilities through knowledge sharing sessions and rotate the economy between people. The activities carried out in this service area by creating a business community in the WhatsApp group (WAG) platform and managing the business activities in it. There are approximately 226 residents of the Puri Depok Mas (Depok) cluster area who are members of this community. PDM Market Partners, which are business communities in the cluster area, have been established since the pandemic, with members as members of sellers and buyers. Sellers are dominated by new businesses, some of which were established during the pandemic. With the existence of a business community through this WAG, it can accommodate all the needs of the seller with regard to the scope of his business and to the buyer for the goods he needs.